DEPENDENSI KEKUASAAN KEHAKIMAN DI ERA ORDE BARU DAN HAK KEADILAN DALAM PERSPEKTIF ISLAM - M Syafi'ie (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2018)
Judicial institutions have a central role in upholding justice laws. The existence of this institution must be maintained by independence, honor, and the law enforcers must not be intervened by the authorities. However, the judiciary has been influenced by power, especially in the era of the New Order regime. Therefore, the formulation of the problem in this paper is two, first, what is the history of the judiciary in Indonesia in the New Order regime? Second, what is the view of Islam that substantially teaches about justice? The method of this research is library research. The result of this study is first, the dependency of the judiciary in the New Order era was very visible. By the 1970s the executive power intervention was very real. Soeharto as the ruler of the New Order managed to influence the implementation of judicial power through the pattern of making legislation that gave a strategic position to executive power. The new order controlled the IKAHI organization through Special Operations (Opsus) led by Ali Murtopo. The IKAHI organization, which initially insisted on rejecting the intervention of power, finally compromised to accept the administrative arrangements of judges under the Ministry of Justice. Second. the actions of the New Order regime were generally contrary to Islamic teachings. Justice rights and equality before the law are guaranteed in Islam. Islam opposes tyranny, arbitrariness, and prohibits the authorities from intervening against the law.